Recursos tecnológicos y la innovación en el aula - Espín Garcés, Josselyn Estefanía (2022)
Education today has undergone several changes due to technological advances, that is, the school must introduce substantial changes in the ways of teaching and learning in order to develop skills that respond to the needs within the classroom. In view of this, teachers must apply technological recourses in their pedagogical process, which contribute significantly to innovation in the classroom. The lack of training and thus the lack of knowledge of teachers regarding the incorporation of technological resources in the classroom does not allow diversification of didactic resources and the use of technology to awaken the interest of students when learning. Therefore, the objective of this research is to incorporate technological resources through tools such as: Canva, Genially and Educaplay to strengthen innovation in the classroom aimed at third year students of the school of Basic Education Isidro Ayora, Latacunga canton, province of Cotopaxi, year 2021.The methodology is based on the interpretive paradigm because we reflected on the use of technological resources in the pedagogical process. The type of research used is qualitative because we deepened the use of technology in the context of educational practice and it was developed in four stages: preparatory, field, analytical and informative. Finally, the method used was inductive, since the observation technique whit its observation guide instrument was applied to collect information regarding the use of technological resources used by teachers in the teaching and learning process. The result is a training workshop for third grade teachers, about the use of technological resources for innovation in the classroom, which contains three digital tools, where the description, how to use them, practical examples, among them: planning stage, execution and evaluation. In this way the research project contributes to strengthen the teaching process through the use of technological resources, for the development of creativity and innovation in the pedagogical process, allowing students to learn in a dynamic and playful way.